Factors affecting the application of the quality control system in Algerian audit firms - field study - khiari, mounir; chebel, amel dounia (Journal of Research in Finance and Accounting, 2025)
This study aims to identify the key challenges facing auditing firms in Algeria in establishing an effective quality control system and attempts to determine the impact of factors that limit the implementation of the quality control system in these firms. To achieve this goal, the researchers conducted a field study on a group of Algerian auditing firms by designing a questionnaire that was randomly distributed to 360 auditing firms scattered across the entire Algerian territory. Out of a total of 360 responses, only 344 questionnaires were accepted. The study found a strong impact of legal factors on the feasibility of implementing a quality control system in Algerian auditing firms compared to professional and competitive factors, which the study showed to have a moderate impact. Legal factors are therefore among the most significant challenges facing the implementation of a quality control system in Algeria